Opioid legislation and narcotic filling in total hip arthroplasty: descriptive study of time and state-level trends in the United States - Daniel J. Cunningham; Sean P. Ryan; Steven Z. George; Brian D. Lewis (BMC, 2021)
Abstract Background The opioid misuse epidemic focused national attention on reducing opioid overprescribing. The purpose of this study is to describe the relationship of time and state-level interventions and opioid filling surrounding total hip arthroplasty (THA) in the United States. Methods A national database with diverse insurance constituents was queried for first-prescription and cumulative perioperative opioid filling volumes and rates in oxycodone 5-mg equivalents (OE's) in 487,942 patients undergoing primary THA from 30-days pre-operative to 90-days post-operative. Descriptive statistics evaluated pre-legislative and post-legislative opioid filling by state, legislative type, and surgery year. Results At the national level, initial opioid filling volumes have remained largely unchanged (56.2 OE's in 2010 to 51.7 OE's in 2018). Meanwhile, cumulative opioid filling volumes (151.9 OE's in 2010 to 111.7 OE's in 2018) have decreased considerably. Rates of initial opioid prescriptions exceeding 90 OE's were similar in 2010 (6.4%) and 2018 (5.6%). States with legislation targeting duration and volume of opioid prescriptions saw the largest decreases in opioid prescription filling. That is, 75% of states with opioid legislation had large (> 10 oxycodone 5-mg equivalents) decreases in cumulative 90-day opioid filling compared to only 20% of states without opioid legislation having large decreases in cumulative 90-day opioid filling. Conclusions This descriptive study demonstrates decreases in perioperative opioid filling for THA. Although this study was descriptive in nature, states enacting opioid-limiting legislation had larger decreases. Although causal relationships could not be inferred from this analysis, the results suggest that states without legislation could improve prescriber compliance with national goals of decreased opioid overprescribing by enacting opioid-limiting legislation. Level of evidence Level III, retrospective prognostic cohort study.